2023
DOI: 10.3389/fmed.2023.977433
|View full text |Cite
|
Sign up to set email alerts
|

Sacral neuromodulation remote programming in patients with refractory lower urinary tract dysfunction: China’s experience during the COVID-19 pandemic

Abstract: ObjectivesSacral neuromodulation is an effective, minimally invasive treatment for refractory lower urinary tract dysfunction. However, regular postoperative programming is crucial for the maintenance of the curative effects of electronic sacral stimulator devices. The outbreak of coronavirus disease 2019 (COVID-19) limited the ability of practitioners to perform traditional face-to-face programming of these stimulators. Therefore, this study aimed to evaluate the application of remote programming technology f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…In other results, our questionnaire survey showed that a significant proportion came from rural areas. And the survey also indicated that most patients chose to undergo sacral nerve modulation therapy due to refractory NLUTD, aligning with previous research 10 . The economic cost of programming for most patients was not as high as initially imagined, but the time cost was substantial, underscoring the significant practical value of remote programming.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In other results, our questionnaire survey showed that a significant proportion came from rural areas. And the survey also indicated that most patients chose to undergo sacral nerve modulation therapy due to refractory NLUTD, aligning with previous research 10 . The economic cost of programming for most patients was not as high as initially imagined, but the time cost was substantial, underscoring the significant practical value of remote programming.…”
Section: Discussionsupporting
confidence: 81%
“…To the best of our knowledge, the presented study is the first multicenter research focusing on the remote programming of Stage I SNM patients. In our team’s previous research, we found that remote programming might help address the aforementioned problem 10 . However, most of these studies were retrospective, and as far as we know, patients receiving sacral nerve modulation therapy are predominantly those with refractory lower urinary tract dysfunction, often accompanied by intense subjective symptoms such as voiding difficulty, urinary frequency, and pain.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations